The Students’ Perception on Teaching Narrative Writing Skills through Contextual Teaching and Learning (CTL) Approach - Yuriatson Jubhari; Nursyam; Luana Sasabone; Rosmiaty; Tuan Nordin bin Tuan Kechik (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2022)
This study aims to investigate the students’ perception on teaching narrative writing skills through contextual teaching and learning (CTL) approach. This study employed a quasi- experimental design with fifty-two eleventh-grade students as participants. The participants were divided into two groups; An experimental group received the CTL approach, and a control group received the conventional way. This study utilized a pre-posttest and perceptional questionnaire. Nonparametric tests (i.e., Mann-Whitney U test and Wilcoxon test) were run to analyze the data in this study. Implementation of the CTL approach through its components positively contributes to teaching narrative writing skills. Meanwhile, the perceptional questionnaires showed that the students' experiment group perceived the implementation of the CTL Approach positively. This study results render teachers’ insight into a practical approach to teaching writing to be able to teach narrative writing. It can be concluded that the students’ perception on teaching narrative writing skills through contextual teaching and learning (CTL) approach have highly positive perception. As recommendation can work at all levels of students’ capability. The implementation of Contextual Teaching and Learning approach can be successful if it is implemented with the appropriate material based on students’ level.